The effects of belief in a just world and victim's innocence on secondary victimization, judgements of justice and deservingness - Correia, I. (2001)
Several studies have shown that victims judged to be innocent are more liked and helped by observers than victims judged to be noninnocent. Nevertheless, objectively innocent victims are very often secondarily victimized (blamed, devalued, avoided, or have their suffering minimized), and judged as deserving or as being in a just situation. An impressive amount of literature shows that high believers in a just world victimize the victims more than low believers, judge them as more deserving and think they are in a fairer situation. But the evaluation of the joint impact of the innocence of the victim and of the observers' BJW (belief in a just world) on the observers' reactions to the victim has been left undone. This study aims to throw some light on this subject. An experimental study was conducted using a 2 BJW (high; low) by 2 victim's innocence (innocent; noninnocent) between-subjects design. No interaction effects were found, but the forms of secondary victimization, as well as the judgements of justice and deservingness, were more positively correlated in the condition where the threat to BJW is higher.